2015
DOI: 10.1089/cyber.2014.0456
|View full text |Cite
|
Sign up to set email alerts
|

Couldn't or Wouldn't? The Influence of Privacy Concerns and Self-Efficacy in Privacy Management on Privacy Protection

Abstract: Sampling 515 college students, this study investigates how privacy protection, including profile visibility, selfdisclosure, and friending, are influenced by privacy concerns and efficacy regarding one's own ability to manage privacy settings, a factor that researchers have yet to give a great deal of attention to in the context of social networking sites (SNSs). The results of this study indicate an inconsistency in adopting strategies to protect privacy, a disconnect from limiting profile visibility and frie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
112
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(117 citation statements)
references
References 44 publications
2
112
1
2
Order By: Relevance
“…Self-efficacy in the context of privacy is the perception of an individual's ability to protect personal privacy (Chen & Chen, 2015). Some previous studies reported that higher self-efficacy lowers privacy risks, consistent with the privacy calculus model, and leads to greater willingness to provide personal information for the use of personalized services (Wasko & Faraj, 2005).…”
Section: Self-efficacymentioning
confidence: 87%
“…Self-efficacy in the context of privacy is the perception of an individual's ability to protect personal privacy (Chen & Chen, 2015). Some previous studies reported that higher self-efficacy lowers privacy risks, consistent with the privacy calculus model, and leads to greater willingness to provide personal information for the use of personalized services (Wasko & Faraj, 2005).…”
Section: Self-efficacymentioning
confidence: 87%
“…their knowledge of the tools available to protect their online information and experience (Hoffman et al 1999;Park 2013), and online privacy self-efficacy (OPSE), i.e. users' belief in their ability to protect their identity when surfing the Internet (Chen & Chen 2015). The studies suggest that higher OPL leads to lower levels of self-disclosure, while lower OPSE has the opposite effect.…”
Section: Factors Of Online Self-disclosurementioning
confidence: 99%
“…Although there have always been concerns about the accuracy of online information, drinking information exchanged on SNSs may be credible for several reasons. First, empirical research shows that college students still share a great deal of personal information on these sites, despite their acknowledgement of privacy concerns [27][28]. Rather than avoiding self-disclosure on SNSs, they develop multiple strategies to balance privacy concerns and their need for self-disclosure, for instance, restricting the access of certain groups to some information [29] and matching the channel of self-disclosure with the sensitivity of the topic [30].…”
Section: Sct and Drinking Normsmentioning
confidence: 99%